2018
DOI: 10.1186/s13104-018-3130-2
|View full text |Cite
|
Sign up to set email alerts
|

Does cognitive behavioral therapy alter mental defeat and cognitive flexibility in patients with panic disorder?

Abstract: ObjectiveMental defeat and cognitive flexibility have been studied as explanatory factors for depression and posttraumatic stress disorder. This study examined mental defeat and cognitive flexibility scores in patients with panic disorder (PD) before and after cognitive behavioral therapy (CBT), and compared them to those of a gender- and age-matched healthy control group.ResultsPatients with PD (n = 15) received 16 weekly individual CBT sessions, and the control group (n = 35) received no treatment. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…[ 86 ] Cooper et al [ 87 ] for instance, reported that the use of antidepressants such as selective serotonin-reuptake inhibitors during the antenatal stage of pregnancy could predispose towards poorer maternal health, quality of life and promote developmental fetal defects. [ 88 ] Furthermore, the use of psychotherapeutic interventions has been preferred because of their ability to promote a challenging environment within which the pregnant women gain cognitive flexibility, [ 39 ] and intrinsic-extrinsic motivation. [ 89 ] Besides, the preference of psychotherapy has also been driven due to the intervention's ability to provide retainable effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 86 ] Cooper et al [ 87 ] for instance, reported that the use of antidepressants such as selective serotonin-reuptake inhibitors during the antenatal stage of pregnancy could predispose towards poorer maternal health, quality of life and promote developmental fetal defects. [ 88 ] Furthermore, the use of psychotherapeutic interventions has been preferred because of their ability to promote a challenging environment within which the pregnant women gain cognitive flexibility, [ 39 ] and intrinsic-extrinsic motivation. [ 89 ] Besides, the preference of psychotherapy has also been driven due to the intervention's ability to provide retainable effects.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, studies also report that psychotherapy can promote the robustness of self-monitoring and attentional allocation cognitive resources, which might further allow a depressed and anxious woman to actively adapt according to a situation. [ 90 , 91 ] Nagata et al [ 39 ] mentioned that cognitive behavioral therapy can effectively combat situations where the loss of emotional automation is prevalent. Here, psychotherapy mediated enhancements in cognitive resources can allow a patient to replace their negative thoughts into objective prospects, thereby, providing a breakthrough from the vicious depression-anxiety cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the patient converts the visual image into a linguistic format (i.e., through speaking or writing it), it disappears more quickly [33]. Based on the negative emotions arising from critically exaggerated interpretations of physical sensations, patients with PD overestimate the true threat and create catastrophic images [34]. In Session 5, in order to establish an identification of images, the patients first, with their eyes closed), were asked to express the most catastrophic image that, for them, can cause a panic attack involving symptoms such as palpitations and hyperventilation (e.g., dying on the street because an ambulance does not arrive).…”
Section: Case Presentationmentioning
confidence: 99%
“…The reappraisal exercises used in the intervention were basically set switching tasks. 4 Emerging research is suggesting that cognitive flexibility, which may be improved with cognitive-behavioral therapy, 6 is associated with less rumination and cognitive reappraisal ability. 7,8 While set switching is involved in positive reappraisal and finding positive gains, it probably cultivates in caregivers a sense of control over negative thoughts as well.…”
Section: Accepted Manuscriptmentioning
confidence: 99%